(3bUjOI aj eOM Hf aQhM CejQ GdMGL GdHjGejs - (3GdOeTbj, YdGA GdOjf Hf GdfMGSs
(3ChdgG (B:s
(3HGJ SGgj GdWQa hGdThb jdM (B*** (3hGdOLG Cf jeVj LfM jGJ LfM , hcGf GdTQb HGH GdOLG (B*** (3eG dg Mha gLhe GdUHM aJMs
(3BNQgG (B:s
(3fGWb Yfi GdaUd GdPj (B*** (3Cf jHGQj adg aj GdahR bHMs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdCOHs